PENGARUH ADVERSITY QUOTIENT DAN MOTIVASI BEPRESTASI TERHADAP KINERJA PENDIDIK PAUD DITINJAU DARI KELOMPOK ETNIS - Puspita, Widya Ayu (JIV-Jurnal Ilmiah Visi, 2009)
The early childhood teacher is expected to be able to to do his/her best in educating ealy age children if he/she has high adversity quotient, This research aimed to explore the influence of adversity intelegence and achievement motivation to early childhood teacher performance. There are 94 respondents participated in this study, age 20 – 40 years old. The data were collected using three instruments, those are Adversity Respons Profile (ARP) Quick Take, Achievement Motivation scale and performance scale. Data was analyzed by two ways anova, dummy linier regression and independent t-test.This research concludes that adversity quotient and motivation influence the performance, but ethnic is only moderaor variables. there is no difference in AQ between Java and Maduresse, but there is a difference on motivation score between Java and Maduresse.